Data management in the international protection procedure in Ireland - Emily Cunniffe; Anne Sheridan (The Economic and Social Research Institute (ESRI), 2021)
In the context of intensified global competition, enhancing attractiveness to foreign direct investment (FDI) in high-value knowledge-intensive sectors is a policy objective in many advanced economies. Understanding what drives the location choice of FDI in high-value knowledge-intensive sectors is important for designing such policies. This research report provides novel evidence on factors and policies underlying the attractiveness of Ireland and Northern Ireland to FDI in high-value knowledgeintensive sectors. Furthermore, this research explores opportunities for policy coordination on the island of Ireland that could enhance the attractiveness of both jurisdictions on the island to high-value FDI. The following knowledge-intensive sectors are included in the analysis: aerospace, biotechnology, pharmaceuticals, medical devices, semiconductors, business machines and equipment, electronic components, consumer electronics, communications, software and IT services, financial services, business services, and space and defence. The research focuses on new greenfield FDI projects - new operations established by foreign companies at new sites on the island of Ireland and the rest of the EU and UK over the period 2003-2020. The analysis uses a newly generated dataset combining information from a range of data sources. Information on new greenfield FDI projects established on the island of Ireland and across EU and UK regions and countries over the past two decades (sourced from the Financial Times fDi Markets database) are combined with data on location-specific factors that influence the location choices of FDI projects (sourced from the European Commission, Eurostat and OECD).
Keywords: 330